ABOUT THE ROLE OF GOVERNMENT SPENDING IN THE PROCESSES OF FINANCIAL POLICY - Vlasiuk, V. Ye. (Science and Transport Progress, 2008)
The paper deals with the analyses of financial system conditions through the state expenses. The factors of the state regulation influence on forming the financial policy are analyzed.